2011
DOI: 10.1177/1933719111401660
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Maternal Hypoxia

Abstract: Antenatal maternal long-term hypoxia (LTH) can alter serotonin (5-HT) and calcium (Ca 2þ ) signaling in fetal pulmonary arteries (PAs) and is associated with persistent pulmonary hypertension of the newborn (PPHN). In humans, the antenatal maternal hypoxia can be secondary to smoking, anemia, and chronic obstructive pulmonary disorders. However, the mechanisms of antenatal maternal hypoxia-related PPHN are unresolved. Because both LTH and 5-HT are associated with PPHN, we tested the hypothesis that antenatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 83 publications
0
37
0
Order By: Relevance
“…After the initial one hour recovery period fetal pCO 2 , Hgb, and pH were similar between the groups (Table 1) Previous induced hypoxic ovine fetus models have been described using hyperthermia, hypoxic chambers, high altitude, and uterine artery embolization. 9,10 In contrast, animals in this study were identified as NOR or spontaneously HYP during the postoperative recovery period, and were studied over a 2 day period. HYP fetuses were identified as those with an SaO2 of ≤55% and evidenced a basal PaO2 of 16.1 mmHg on the study day, consistent with criteria for hypoxia utilized in previous studies of spontaneously hypoxic ovine fetuses.…”
Section: Resultsmentioning
confidence: 98%
“…After the initial one hour recovery period fetal pCO 2 , Hgb, and pH were similar between the groups (Table 1) Previous induced hypoxic ovine fetus models have been described using hyperthermia, hypoxic chambers, high altitude, and uterine artery embolization. 9,10 In contrast, animals in this study were identified as NOR or spontaneously HYP during the postoperative recovery period, and were studied over a 2 day period. HYP fetuses were identified as those with an SaO2 of ≤55% and evidenced a basal PaO2 of 16.1 mmHg on the study day, consistent with criteria for hypoxia utilized in previous studies of spontaneously hypoxic ovine fetuses.…”
Section: Resultsmentioning
confidence: 98%
“…Our understanding of Ca 2+ signaling in fetal pulmonary arterial myocytes is still limited, but studies performed on fetal sheep pulmonary vascular myocytes illustrate that platelet activating factor (PAF) causes InsP 3 generation and Ca 2+ responses [77, 78]. This is substantiated by our own studies showing that ATP, phenylephrine and serotonin all cause Ca 2+ responses in pulmonary arterial myocytes from fetal sheep [64, 79]. Even still, ET-1-dependent activation of G protein coupled receptors can also induce RyR-generated Ca 2+ sparks [80], illustrating the complexity of Ca 2+ signaling within pulmonary vascular myocytes.…”
Section: The Mammalian Lung: Developmental Progression and Functionmentioning
confidence: 96%
“…Moreover the fetal circulation is also characterized by progressive changes in vasore-activity. For example, we find that ovine fetuses have reduced constriction to membrane depolarization with high potassium [63] or serotonin [64, 65] as compared to adults. Also in the ovine fetus, vasoreactivity increases in late gestation (136-146 days) compared to early gestation (94-101 days), with increased hyperoxia-induced vasodilation and pulmonary vascular blood flow [66].…”
Section: The Mammalian Lung: Developmental Progression and Functionmentioning
confidence: 99%
See 2 more Smart Citations